INRUSH CURRENT LIMITATION BY UTILIZATION OF LINEAR MODE OF IGBT TRANSISTOR - Kroičs, Kaspars; Saltanovs, Rodions (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Input filter is essential part of each switched mode power supply design. Important issue that must be solved in the design process is control of the high inrush current due to rapid rise of the voltage during initial connection of the power to the power supply. In the paper a single IGBT or MOSFET transistor is applied to control dv/dt in order to limit the high current spikes during initial power turn on or to limit overcurrent in microarc oxidation process. This inrush current limiting technique is beneficial because dv/dt control reduces the electromagnetic interference due to current and voltage spikes. As inrush current limiting device has minimal parts count the design is cost effective and reliable.